OTONOMI DAERAH DAN PERMASALAHANNYA DALAM PENGELOLAAN KELAUTAN - Masyhuri Imron (Jurnal Masyarakat dan Budaya, 2011)
Since 1999, based on Law No. 22 of 1999 as revised by Law No. 32 of 2004, Indonesia has implementeed local autonomy in the marine sector. In those regulations, central government delegates his authority to manage 12 miles of the sea to provincial and one third of it to the district/municipalgovernment. However, there are many problems which impacted to the ineffectiveness of the local marine management. The most serious problem is the exclusion of local community roles in marine management. As one recommendation of this writing, the increase of community participation should be supported, and traditional management system should be revitalized. Keywords: Local autonomy; Marine Management; Community Participation.